The basement geology of the Porcupine High - a key transatlantic link between the Caledonides and Appalachians - Dennehy, Shannon Raftery (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2023)
In order to better reconstruct the basement geology of the western Irish offshore and the North Atlantic, constraining the geologic evolution of the Porcupine High region is key. Located 200 km west of Ireland, the Porcupine High is a NNE-trending bathymetric high, and is surrounded by several basins that have been the site of petroleum exploration since the 1970s. In this paper, we present geochronological data from sampling campaigns, including dredge samples and shallow drill cores, over the last twenty years. All samples were recovered north of the inferred trace of the Iapetus suture. Most dredge samples are likely near in situ. A core of foliated gneiss yields U-Pb zircon ages of c. 500-478 Ma. A 385 Ma apatite U-Pb age records post-Caledonian exhumation; K-feldspar Pb isotope data imply a Caledonian affinity. These rocks are assigned to the ophiolitic rocks of the Clew Bay Complex and were sampled adjacent to a E-W trending magnetic boundary across the Porcupine High that we correlate with the Fair Head - Clew Bay line. North of this sampling site, in a region with a magnetic anomaly low, dredging recovered >90% lower greenschist-facies psammite cobbles. U-Pb detrital zircon data imply an affinity with the Moine or Grampian Group and U-Pb apatite ages (900 - 1800 Ma) are unaffected by Caledonian orogenesis. Drilled granitic orthogneiss collected farther north yields a 1314 Ma U-Pb zircon crystallization age. Granulite-facies metamorphism (12 kbar, 740°C) is of likely Grenville age and is supported by an apatite U-Pb cooling age of 875 Ma. Zircon Hf isotopic and Pb-Kfsp data point to an affinity with the Rockall Bank Palaeoproterozoic, delimiting the offshore extent of the Annagh Gneiss Complex (AGC) of NW Ireland. Dredge samples collected at the northernmost site yield >98% metamorphic clasts. U-Pb detrital zircon ages from two low-grade metasediments imply a Moine/Grampian Group and an Upper Dalradian affinity respectively; Caledonian apatite U-Pb ages are prevalent. The high-grade rocks, including orthogneisses and amphibolites, can be broken into three groups: clasts with 2750 Ma U-Pb zircon crystallization ages, 1750 Ma apatite U-Pb ages and a Lewisian Pb-in-Kfsp signature; clasts with 1830-1940 Ma U-Pb zircon ages, 1750 Ma apatite U-Pb ages and an AGC Pb-in-Kfsp affinity, and AGC clasts with 1550-1650 Ma U-Pb zircon ages and U-Pb apatite ages recording post-Grenville cooling. All three groups were found at one dredge site and a component of Quaternary glacial transport is suggested for these dredged clasts.
The basement geology of the Porcupine High - a key transatlantic link between the Caledonides and Appalachians
APPROVED
Keywords: Precambrian; Isotope Geochemistry; Porcupine High; Ireland; Offshore basement geology; Irish offshore; Caledonides